2013
DOI: 10.13157/arla.60.2.2013.291
|View full text |Cite
|
Sign up to set email alerts
|

Hole Selection by Nesting Swifts in Medieval City-Walls of Central Spain

Abstract: SUMMARY.-Disturbance and predation risks from terrestrial animals decline the higher up the nest sites selected by birds that nest in wall cavities are located. Terrestrial predators can also negate the protective quality of higher nesting sites by approaching from above in walls. It is unknown how terrestrial predation risks from below and above walls determine nest site selection in cavity-nesting species. In relation to this situation, we describe nest-site selection in common swifts Apus apus in the mediev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The size of a ravine is a fundamental aspect for reproduction in colonies. Our study shows that from the available pool of ravines, burrowing parrots are selecting those that are larger and taller, which allow individuals to build their nests farther from the ground, probably as a response to terrestrial predation ( Corrales et al, 2013 ). Our results also confirm that the largest ravines are the ones with the highest number of nests and egg production.…”
Section: Discussionmentioning
confidence: 89%
“…The size of a ravine is a fundamental aspect for reproduction in colonies. Our study shows that from the available pool of ravines, burrowing parrots are selecting those that are larger and taller, which allow individuals to build their nests farther from the ground, probably as a response to terrestrial predation ( Corrales et al, 2013 ). Our results also confirm that the largest ravines are the ones with the highest number of nests and egg production.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, Swifts showed a preference for boxes situated higher than 11 m. Other studies reported preferences for rather lower heights (Colombo and Galeotti 1993, Wortha and Arndt 2004). Corrales et al (2013) found no preferences within 3.5–12.2m height in a medieval city wall. However, in the latter study, higher cavities situated less than 1.7 m below the upper edge of the wall were avoided, probably because they were accessible to terrestrial predators.…”
Section: Discussionmentioning
confidence: 97%
“…Wormlions are an additional example of a successful trapbuilding predator in cities. Wormlions are not the only species using walls or wall-adjacent microhabitats in cities, and other examples include a variety of plant, bird, lizard, and arthropod species [17,19,21,60]. Walls, in contrast, provide worse conditions for amphibians in ponds compared to ponds with no vertical walls, so the advantage walls provide is species-specific [61].…”
Section: Discussionmentioning
confidence: 99%
“…Such species are also able to exploit the artificial habitat of a city if it resembles their habitat in the wild [15]. Cliff-nesting birds such as swifts and kestrels, which nest in buildings, serve as an excellent example [16,17].…”
Section: Introductionmentioning
confidence: 99%